2019
DOI: 10.3390/su11205603
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Physical Environment-Related Factors in an Assessment of Community Attachment: Understanding Urban Park Contributions

Abstract: Community sociologists have examined community attachment through an almost exclusive focus on people’s social relations. Recent research efforts have noted the neglect of the physical place in traditional community sociological studies. Doing this has brought the physical environment into their discussions of community attachment. Despite this progress, we remain limited in our understanding of the physical environment’s contribution to peoples’ attachment to their communities and whether its effect on commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Urban parks are important elements of city infrastructure, providing numerous and diverse functions and benefits. A not exhaustive list includes positive impacts on health and wellbeing, through recreation, leisure, and sport activities [1]; community development, sense of place, identity, and social cohesion, through cultural activities and providing space and occasion for social interaction and mutual understanding [2]; education, as people can discover plants, animals and natural phenomena or use parks as outdoor classrooms [3]; the economy, as the presence of parks generates investment opportunities, attracts customers, including tourists [4], and increases the price of properties in the vicinity [5,6]; ecosystem functioning, through a range of ecosystem services, from biodiversity conservation to resource production [7], improving air quality (absorbing pollutants, regulating humidity) [8], carbon sequestration, water management (storm water absorption, and run off regulation), and mitigating urban heat islands [9].…”
Section: Introductionmentioning
confidence: 99%
“…Urban parks are important elements of city infrastructure, providing numerous and diverse functions and benefits. A not exhaustive list includes positive impacts on health and wellbeing, through recreation, leisure, and sport activities [1]; community development, sense of place, identity, and social cohesion, through cultural activities and providing space and occasion for social interaction and mutual understanding [2]; education, as people can discover plants, animals and natural phenomena or use parks as outdoor classrooms [3]; the economy, as the presence of parks generates investment opportunities, attracts customers, including tourists [4], and increases the price of properties in the vicinity [5,6]; ecosystem functioning, through a range of ecosystem services, from biodiversity conservation to resource production [7], improving air quality (absorbing pollutants, regulating humidity) [8], carbon sequestration, water management (storm water absorption, and run off regulation), and mitigating urban heat islands [9].…”
Section: Introductionmentioning
confidence: 99%
“…The present study builds on earlier work (e.g., Brehm et al 2004Brehm et al , 2006Clark and Stein 2003;Matarrita-Cascante et al 2010;Xu et al 2019) that suggests the physical environment's importance in predicting community attachment. Most studies taking this newer approach, however, have focused on the role of the natural environment with respect to amenity-rich rural communities.…”
Section: Introductionmentioning
confidence: 79%
“…For example, Matarrita-Cascante et al (2010) found that natural environment-based interactions and residence choice motivations (linked to natural amenities) resulted in increased community attachment for both long-term residents and seasonal residents in natural resource-rich areas. Similarly, Xu et al (2019) have shown that community attachment is not determined completely by social factors but also by physical environmental factors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Community attachment and place attachment are similar concepts in that they both aim to capture the positive affections people build towards places [4,[12][13][14][15][16]. Similar to place attachment, community attachment can be defined at different scales.…”
Section: Defining Community Attachmentmentioning
confidence: 99%